2022
DOI: 10.3389/fpls.2022.894706
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Response of Soybean and Cotton to Different Irrigation Regimes and Planting Geometries

Abstract: Soybean [Glycine max (L.) Merr.] and cotton (Gossypium hirsutum L.) are the major row crops in the USA, and growers are tending toward the twin-row system and irrigation to increase productivity. In a 2-year study (2018 and 2019), we examined the gas exchange and chlorophyll fluorescence parameters to better understand the regulatory and adaptive mechanisms of the photosynthetic components of cotton and soybean grown under varying levels of irrigations and planting geometries in a split-plot experiment. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…This result is crucial to elucidating the enhancement of the photosynthesis of wheat under Cd stress via NaHS pretreatment since higher Pn increases the potential of wheat to assimilate CO 2 . LCP and LSP reflect the adaptability of plants to low and high light intensity, respectively, while AQE reflects the ability of plants to use light [43]. In the present study, Cd stress significantly reduced AQE and LSP of wheat seedlings.…”
Section: Nahs Pretreatment Improved the Light Use Efficiency Of Wheat...supporting
confidence: 49%
“…This result is crucial to elucidating the enhancement of the photosynthesis of wheat under Cd stress via NaHS pretreatment since higher Pn increases the potential of wheat to assimilate CO 2 . LCP and LSP reflect the adaptability of plants to low and high light intensity, respectively, while AQE reflects the ability of plants to use light [43]. In the present study, Cd stress significantly reduced AQE and LSP of wheat seedlings.…”
Section: Nahs Pretreatment Improved the Light Use Efficiency Of Wheat...supporting
confidence: 49%
“…Sprinkler irrigation alters the crop’ s microclimate by lowering canopy temperature ( Table 7 ) and maintaining plant water status ( Li et al., 2013 ; Bana et al, 2020 ; Liu et al., 2021 ; Tang et al., 2022 ) and eventually leads to better net-photosynthetic rate in soybean ( Cotrim et al., 2021 ; Rajanna et al., 2022b ; Wang et al., 2023 ). Additionally, Pinnamaneni et al. (2022) observed that soybean cultivated in a rainfed environment or without irrigation exhibited a decrease in stomatal conductance and transpiration, which in turn decreased the crop’s ability to perform photosynthetically.…”
Section: Discussionmentioning
confidence: 99%
“…NPQ is a frequently used method to evaluate the effects of herbicides on the functioning of PSII, particularly the activation of photoprotective mechanisms [22]. Therefore, NPQ has recently been used in plants, including crops and weeds, for the evaluation of their sensitivity/resistance to particular herbicides (e.g., [23] for soybean and cotton, [24] for two weed species) and a marker for optimized photosynthesis and biomass production [25].…”
Section: Introductionmentioning
confidence: 99%